Network-based analysis of ASD GWAS: Biosys module on systems medicine, genomics and personalized medicine - Correia, Catarina (2015)
Funding: Autism Speaks, Medical Research Council, Health Research Board (Ireland), NIH (USA), Genome Canada, Hillibrand Foundation, Fundação para a Ciência e Tecnologia